Skylights With An Aesthetic Value - The Star, Myra Vong (2008)
Living in a tropical climate like Malaysia increase our need to have some from of shelter to protect us from adverse weather conditions. While you may be able to escape from the heat and the rain bu staying in the house, your cars and plants may not be so lucky.